PRINS and In Situ PCR Protocols - Pellestor, Franck; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2006)
Carrying on the high standards of the much-praised first edition, leading researchers and clinical investigators have completely revised and updated PRINS and In Situ PCR Protocols to take advantage of the many new developments and applications that have occurred for cellular and molecular investigations. The authors contribute proven protocols for many variations of PRINS and in situ PCR, including a new, fast multicolor PRINS method for identifying human chromosomes, PRINS protocols for in situ detection of unique sequences and point mutations, a new dideoxy PRINS procedure, and in situ PCR and PRINS protocols for plants. They describe, in detail, various applications of PRINS in human cells (detection of gene deletions in cancer, detection of fetal cells in maternal blood, and assessment of aneuploidy in brain tissues and embryos) as well as in plant cells. Readily reproducible in situ PCR techniques are also presented for the detection of cytomegalovirus and for use in combination with microdissection. In situ RT-PCR techniques are also given for use in plant or cancer investigation. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and highly practical, PRINS and In Situ PCR Protocols offers molecular biologists, cytogeneticists, and cytologists a cutting-edge guide to today's new in situ labeling technology.
Basic Methodology -- New Rapid Multicolor PRINS Protocol -- PRINS Combined With Peptide Nucleic Acid Labeling -- PRINS Combined With Indirect Immunofluorescence -- PRINS for the Detection of Unique Sequences -- Single-Copy and Point Mutation Analysis (Rolling-Circle PRINS) -- Analysis of Sperm Aneuploidy by PRINS -- In Situ PCR Protocols -- Research and Clinical Applications -- Detection and Sizing of Telomeric and Other Simple Repeats by Dideoxy-PRINS -- PRINS Evaluation of Chromosome Instability in Mammalian Cells by Detection of Repetitive DNA Sequences in Micronuclei -- PRINS for the Detection of Gene Deletions in Cancer -- Combined Fluorescence In Situ Hybridization and PRINS for the Analysis of the Dystrophin Gene -- Brain Tissue Preparations for Chromosomal PRINS Labeling -- PRINS on Plant Chromosomes -- Dual-Color PRINS for In Situ Detection of Fetal Cells in Maternal Blood -- PRINS as an Efficient Tool for Aneuploidy Assessment in Human Oocytes and Preimplantation Embryos -- Microdissection With PCR In Situ -- Application of Reverse Transcription In Situ PCR in Cancer Analysis -- In Situ Reverse Transcription PCR on Plant Tissues -- In Situ PCR for the Detection of Human Cytomegalovirus in Suspension Cells During the Latent Phase of Infection -- Development and Adaptation of the PRINS Technology -- Latest Developments in In Situ PCR.
Keywords: Biochemistry; Cell biology; Biochemistry, general; Cell Biology